The Time of Paradox. A Time of Redefinition - Dudziak, Maciej (Journal of Applied Cultural Studies, 2015)
The author is of the opinion that contemporary times could be described by the concept of a paradox forcing a redefinition of the fundamental concepts sanctioning the functioning of what until now would have seemed permanent states of focus of culture. On the one hand the satiated and ostensibly safe Western Civilisation is dealing with ever more problems it has produced for itself, whether in the form of post-colonial legacy that it is having to contend with, or the effects of hazy and inefficient multiculturalism projects, while on the other hand for over a decade, symbolically since the turn of the 21st century, the world has been undergoing fragmentation, and the tribal sentiments of diverse groups, who previously had no say of their own or were denied the right to have one, are being heard.